OzoNews Volume XX - 30 March 2020 - United Nations Environment Programme (2020)
In this issue: 1. COVID-19 pandemic: Letter from James S. Curlin, Acting Head, OzonAction, to the National Ozone Officers 2. Global efforts on ozone help reverse southern jet stream damage 3. Rare ozone hole opens over Arctic — and it’s big 4. “COLD CHAIN 4 LIFE” Campaign 5. Quantifying contributions of chlorofluorocarbon banks to emissions and impacts on the ozone layer and climate 6. Countries must take action on ‘hidden’ CFC stocks 7. Assessment of climate and development benefits of efficient and climate-friendly cooling 8. Emissions of several ozone-depleting chemicals are larger than expected 9. Remembering Eric Prieur, Food Logistics’ 2020 Champion of the Year 10. 2020 Asia Environmental Enforcement Awards 11. Vietnam introduces law aimed at fighting climate change 12. e-system for environmental clearance linked to customs (Saudi Arabia) 13. Rare Arctic ozone hole stretches from Hudson Bay to Siberia 14. ASHRAE Offers Course on the Role of HVAC Systems on Infection Control 15. REHVA (Federation of European Heating, Ventilation and Air Conditioning Associations) COVID-19 Guidance